2019
DOI: 10.1155/2019/2034247
|View full text |Cite
|
Sign up to set email alerts
|

Extract fromBougainvillea xbuttiana(Variety Orange) Inhibits Production of LPS-Induced Inflammatory Mediators in Macrophages and Exerts a Protective EffectIn Vivo

Abstract: Background. Different pharmacological properties, such as antioxidant, antiproliferative, and anti-inflammatory properties, have been described among natural products. We previously described that the Bougainvillea xbuttiana (Variety Orange) ethanolic extract (BxbO) has an anti-inflammatory effect; however, this action is not fully understood. In this study, the action of the BxbO extract on the secretion of inflammatory mediators in two experimental models, in vitro and in vivo, after LPS challenge was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Also, when evaluating the transfusion rate, contributing factors such as preoperative hemoglobin values, hematocrit, intravascular volume status, respiratory oxygen delivery status as well as hemodynamic instability should be accounted for 1 . Several studies confirmed our results for the significant predictive values of the ADPHS test in terms of the higher necessity for transfusion 14,16–18 . As in our trial for the adjusted cut‐off test values, Petricevic et al 17 also failed to demonstrate the predictive value of the test for a higher RBC transfusion rate.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, when evaluating the transfusion rate, contributing factors such as preoperative hemoglobin values, hematocrit, intravascular volume status, respiratory oxygen delivery status as well as hemodynamic instability should be accounted for 1 . Several studies confirmed our results for the significant predictive values of the ADPHS test in terms of the higher necessity for transfusion 14,16–18 . As in our trial for the adjusted cut‐off test values, Petricevic et al 17 also failed to demonstrate the predictive value of the test for a higher RBC transfusion rate.…”
Section: Discussionsupporting
confidence: 76%
“…Also, Rafiq et al confirmed the positive predictive value for the ADPHS test while other platelet function tests failed to demonstrate significant predictive values for high blood loss. A lower threshold than the one provided by the manufacturer was demonstrated in the large trial with Several studies confirmed our results for the significant predictive values of theADPHS test in terms of the higher necessity for transfusion 14,[16][17][18]. As in our trial for the adjusted cut-off test values, Petricevic et al17 also failed to demonstrate the predictive value of the test for a higher RBC transfusion rate.…”
supporting
confidence: 87%
“…There are approximately 18 species of Bougainvillea, but only the above two species are well-known for cultivation [1,5]. The purpose of planting Bougainvillea is mostly ornamental, but recently a number of studies have explored the potential use of Bougainvillea as a medicinal plant and as a pollution-mitigating plant in industrial areas [6][7][8][9][10][11]. Recent research studies have tapped into the potential of Bougainvillea as an anti-inflammatory, anticancer, antioxidant, antimicrobial, and antihyperglycemic plant [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During RDV intervention one hour post LPS challenge, mice were also randomly divided into four groups (n = 6 in each group): control, RDV, LPS, and RDV + LPS groups. Mice in RDV and RDV +LPS groups were administered with RDV at a dosage of 25 mg/kg post 10 mg/kg LPS challenge one hour by subcutaneous injection (21). After LPS injection for 12 h, the mice were sacrificed and kidney tissue was collected for evaluation of kidney inflammation score.…”
Section: Animals and Experimental Designmentioning
confidence: 99%